The use of moist exposed burn ointment (MEBO) for the treatment of burn wounds: a systematic review. Issue 6 (1st December 2020) - Mabvuure, Nigel Tapiwa; Brewer, Christopher Felix; Gervin, Kevin; Duffy, Siobhan
Abstract: Moist exposed burn ointment (MEBO) is an oil-based herbal paste, purported to be efficacious in managing burn wounds and more commonly used in Asia and the Middle East. A PRISMA-compliant systematic review was performed to analyse the evidence for the use of MEBO on burn wounds. Wound healing rate was the primary outcome of interest. PubMed-listed randomised controlled trials (RCTs) comparing the efficacy of MEBO with placebo, standard care or other therapies in the treatment of partial thickness burns in adults and children were eligible for inclusion (November 2019). Six RCTs were eligible. The majority of trials comparing wound healing between MEBO and SSD favoured MEBO (two of three). There may be improved healing in MEBO-treated wounds vs. those treated with povidone-iodine + bepanthenol cream. There was no difference between MEBO and Acquacel Ag, but Helix Aspersa had faster healing rates than MEBO. However, all evidence was from moderately to poorly reported trials with a high risk of bias, thereby limiting the strength of this evidence. In conclusion, the evidence for MEBO in English-language literature was poor and inconsistent with respect to wound healing rate and analgesis compared to 1% SSD, Acquacel Ag, Helix aspersa cream and povidone-iodine + bepanthenol cream. Blinded RCTs comparing MEBO to both placebo and other common topical treatments may further improve the confidence in concluding their analysis. There is some evidence that MEBO is as safe as its comparators as shown by the low complication rate.